Clinical features in 27 patients with Angelman syndrome resulting from DNA deletion. Issue 2 (February 1996) - Smith, A; Wiles, C; Haan, E; McGill, J; Wallace, G; Dixon, J; Selby, R; Colley, A; Marks, R; Trent, R J
Abstract : We report the clinical features in 27 Australasian patients with Angelman syndrome (AS), all with a DNA deletion involving chromosome 15(q11-13), spanning markers from D15S9 to D15S12, about 3 center dot 5 Mb of DNA. There were nine males and 18 females. All cases were sporadic. The mean age at last review (end of 1994) was 11 center dot 2 years (range 3 to 34 years). All patients were ataxic, severely retarded, and lacking recognisable speech. In all patients, head circumference (HC) at birth was normal but skewed in distribution, with 62 center dot 5% at the 10th centile. At last review HC was around the 50th centile in three patients (12 center dot 5%) while 15 had poor postnatal head growth. Short stature was not invariable, 5/26 (19%) were on or above the 50th centile. Hypotonia at birth was recorded in 15/24 (63%) and neonatal feeding difficulties were recorded in 20/26 (77%). Epilepsy was present in 26/27 (96%) with onset by the third year of life in 20 patients (83%). Improvement in epilepsy was reported in 11/16 patients (69%) with age. An abnormal EEG was reported in 25/25 patients. Hypopigmentation was present in 19/26 (73%). One patient had oculocutaneous albinism. Five patients could not walk independently. Of the remaining 22 who could walk, age of onset of walking ranged from 2 to 8 years. Disrupted sleep patterns were present in 18/21 patients (86%), with improvement in 9/12 patients (75%) over 10 years of age. The clinical features in this group of deletional AS patients were similar to previous reports, but these have not separated patients into subgroups based on DNA studies. In our group of deletional cases, 100% showed severe mental retardation, ataxic movements, absent language, abnormal EEG, happy disposition (noted in infancy in 95%), normal birth weight and head circumference at birth, and a large, wide mouth. These features occurred with a higher frequency than in AS patients as a whole. Our study also provided information on the evolution of the phenotype. The data can act as a benchmark for comparisons of AS resulting from other genetic mechanisms.